Outcome of Late Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs)
The clinical and EEG features, the occurrence of subsequent seizures, and the neurologic outcome in 50 children who had febrile seizures (FS) after 5 years of age were studied at the University of British Columbia, Canada.